The Good, the Bad, and the Epigenetic: Stress-Induced Metabolite Regulation and Transgenerational Effects - Saida Ibragić; Sabina Dahija; Erna Karalija (Epigenomes, 2025)
Background: Plants face a wide range of environmental stresses that disrupt growth and productivity. To survive and adapt, they undergo complex metabolic reprogramming by redirecting carbon and nitrogen fluxes toward the biosynthesis of protective secondary metabolites such as phenylpropanoids, flavonoids, and lignin. Recent research has revealed that these stress-induced metabolic processes are tightly regulated by epigenetic mechanisms, including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNAs. Methods: This review synthesizes current findings from studies on both model and crop plants, examining the roles of key epigenetic regulators in controlling secondary metabolism under stress. Special focus is placed on dynamic changes in DNA methylation, histone acetylation, and the action of small RNAs such as siRNAs and miRNAs in transcriptional and post-transcriptional regulation. Results: Evidence indicates that stress triggers rapid and reversible epigenetic modifications that modulate gene expression linked to secondary metabolic pathways. These modifications not only facilitate immediate metabolic responses but can also contribute to stress memory. In some cases, this memory is retained and transmitted to the next generation, influencing progeny stress responses. However, critical knowledge gaps remain, particularly concerning the temporal dynamics, tissue specificity, and long-term stability of these epigenetic marks in crops. Conclusions: Understanding how epigenetic regulation governs secondary metabolite production offers promising avenues to enhance crop resilience and productivity in the context of climate change. Future research should prioritize dissecting the stability and heritability of these modifications to support the development of epigenetically informed breeding strategies.